Responding to Gun Crime in Ireland - Campbell, Liz (The British journal of criminology, 2010)
From stereotypical views of Ireland as a peaceful and ‘low crime ’ society, the media and policy makers now report the worsening of gun crime, in particular crimes of homicide committed by firearm. Despite this sometimes hyperbolic popular commentary, serious and fatal gun crime has indeed increased. In reacting through extraordinary legal measures, the Irish state adopts an unduly narrow perspective, predicated on a rational actor model; what this paper seeks to do is put forward two more profitable and persuasive means of analysis, by focusing on social deprivation and the expression of masculinity